Growth and nutritional management of children on peritoneal dialysis - Ariane Zaloszyc; Saoussen Krid; Bruno Ranchin (RDPLF, 2019)
Stunting and malnutrition are common in children with chronic kidney disease and increase with the degree of impairment to be maximal in children at the dialysis stage, leading to a risk of excess mortality. Despite many advances in the field of pediatric dialysis, small size in adulthood remains very common in this population. The origin of malnutrition and stunting is complex and multifactorial. In infants on peritoneal dialysis, insufficient nutritional intake is recognized as a major barrier to adequate growth. The diagnostic approach to undernutrition and stunting in peritoneal dialysis requires the use of several elements: an interrogation, a clinical examination, and various complementary examinations. Due to the multifactorial aspect of the nutritional and statural status of the child, several therapeutic axes are to be taken into account, namely a nutritional treatment adapted to the needs of the child, a treatment by growth hormone, and an optimization of dialysis to allow optimal metabolic control.